Success factor of web integrated library system and job satisfaction in academic libraries / Mawar Noor Abdullah - Abdullah, Mawar Noor (2020)
Web integrated library system performance is important to evaluate as it’s is use in managing library activities and holds millions of library records. To have effective web integrated library system for staff, it is essential for the library to offer high quality of system, service, usage and Internet. This study presents a perception on web integrated library system success factor (system quality, service quality, usage quality and Internet quality) and its relationships with job satisfaction. Questionnaires was distributed to 110 library staff who are using the web integrated library system at academic libraries in Selangor, Melaka, Johor, Negeri Sembilan and Pahang. The analyses are undertaken using SPSS. Descriptive findings show moderate perceptions in four variables (system quality, service quality, usage quality and job satisfaction) where the mean value are in the range 3.18 to 3.45 and low perception in one variable (Internet quality) in range 2.69 on a 5-point Likert. Besides that, the results also indicate a positive and high correlation between job satisfaction with usage quality, moderate correlation between service quality and Internet quality. Meanwhile, the relationship between job satisfaction and system quality is weak. The finding of the study is useful for the library to realize that success factor of web integrated library system will contribute to their job satisfaction. As to that, the library should improve their library information system to provide a high quality of library product and services.